Can be written as A B \frac{A}{B} , where A A and B B are not coprime?!

The sum of the reciprocals of all numbers that have a prime factorization of A m B n A^m B^n , where m m and n n are positive integers and A A and B B are positive integers that are not necessarily coprime can be expressed as A B \dfrac{A}{B} . What is A + B A+B ?


Inspiration: Mind your 3's and 2's .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Michael Tong
Dec 28, 2013

m = 1 n = 1 1 A m B n = m = 1 1 A m n = 1 1 B n \displaystyle \sum_{m = 1}^{\infty} \displaystyle \sum_{n=1}^{\infty} \frac{1}{A^m B^n} = \displaystyle \sum_{m = 1}^{\infty} \frac{1}{A^m} \displaystyle \sum_{n = 1}^{\infty} \frac{1}{B^n}

We know that 1 A , 1 B < 1 \frac{1}{A}, \frac{1}{B} < 1 because the sum would be infinite otherwise and thus it would not be able to expressed as A B \frac{A}{B} . So using the geometric series formula

( 1 A 1 1 A ) ( 1 B 1 1 B ) = ( 1 A 1 ) ( 1 B 1 ) = A B (\frac{\frac{1}{A}}{1 - \frac{1}{A}})(\frac{\frac{1}{B}}{1 - \frac{1}{B}}) = (\frac{1}{A-1})(\frac{1}{B-1}) = \frac{A}{B} .

Cross multiplying, we get A ( A 1 ) ( B 1 ) = B A(A-1)(B-1) = B and then B = A 2 A A 2 A 1 = 1 + 1 A 2 A 1 B = \frac{A^2 - A}{A^2 - A - 1} = 1 + \frac{1}{A^2 - A - 1}

Since B B is an integer, then A 2 A 1 = 1 A^2 - A - 1 = 1 , so A = 2 A = 2 and B = 2 B = 2 .

Thus, A + B = 4 A + B = 4 .

This was a cool problem! A little trivial, but still quite fun!

Sam Thompson - 7 years, 4 months ago

You actually have a correct answer on your problem ;)

If you wanted to put a link to a problem, you could put it like this: What you want to call the website . I think that would have been helpful at the top.

Trevor B. - 7 years, 5 months ago

Both A , B A, B are prime numbers, since the problem states that A m B n A^mB^n is a prime factorization. Since B = A ( A 1 ) ( B 1 ) B=A(A-1)(B-1) , we have A 1 = 1 A-1=1 and B 1 = 1 B-1=1 . Hence A = B = 2 A=B=2 . But there is no need to limit to prime factorization as your solution shows.

George G - 7 years, 5 months ago
Trevor B.
Dec 28, 2013

This can be represented as the product of two geometric series like this. i = 1 j = 1 1 A i B j = i = 1 1 A i × j = 1 1 B j \sum_{i=1}^{\infty}\sum_{j=1}^{\infty}\dfrac{1}{A^iB^j} =\sum_{i=1}^{\infty}\dfrac{1}{A^i}\times\sum_{j=1}^{\infty}\dfrac{1}{B^j}

We can take the sum of these series individually. Let the first sequence be X X and the second one be Y . Y. We are looking for x × Y . x\times Y.

X X is a geometric sequence with first term 1 A \frac{1}{A} and ratio 1 A . \frac{1}{A}. The sum of the terms is equal to 1 A 1 1 A = 1 A A 1 A = 1 A-1 \dfrac{\frac{1}{A}}{1-\frac{1}{A}}=\dfrac{\frac{1}{A}}{\frac{A-1}{A}}={\dfrac{\textbf{1}}{\textbf{A-1}}}

Similarly, Y Y is a geometric sequence with first term 1 B \frac{1}{B} and ratio 1 B . \frac{1}{B}. The sum of the terms is equal to 1 B 1 1 B = 1 B B 1 B = 1 B-1 \dfrac{\frac{1}{B}}{1-\frac{1}{B}}=\dfrac{\frac{1}{B}}{\frac{B-1}{B}}={\dfrac{\textbf{1}}{\textbf{B-1}}}

X × Y = 1 ( A 1 ) ( B 1 ) . X\times Y=\frac{1}{(A-1)(B-1)}. We have found what the sum of the reciprocals of A m B n A^mB^n is. Now we need to solve for A A and B B in this equation. 1 ( A 1 ) ( B 1 ) = A B \dfrac{1}{(A-1)(B-1)}=\dfrac{A}{B} We find that B = A 2 A A 2 A 1 *** B=\frac{A^2-A}{A^2-A-1}\text{***}

Solving this equation yields { A , B } = { 2 , 2 } \{A,B\}=\{2,2\} as solutions, so A + B = 4 A+B=\boxed{4}

* We don't have to worry about a non-unique solution because this function is asymptotic at A = 1 A=1 and B = 1 B=1 (in the A-B coordinate plane, which is exactly the same as the Cartesian plane). A A and B B have to be greater than or equal to 2 2 because if either of them were 1 1 then the total sum would be infinite. Any A > 2 A>2 would produce a non-integer B -value B\text{-value} in the range 1 < B < 2. 1<B<2. A graph of this function is here .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...